Understanding air leak in COVID-19 patients: case series - Kanani, Elmutaz A. M.; Al Kharusi, Adil S. Z. (International Surgery Journal, 2022)
Around one fifth of COVID-19 patients progress to develop acute respiratory distress syndrome. This cohort carries the highest morbidity and mortality, and the greatest treatment challenges. They are more likely to require mechanical ventilation. Thoracic air leak has been noted to be more prevalent in this group of patients. This study aims to explore the relationship between ventilator settings and the development of air leak as possible triggers, and the basic pathophysiological concepts behind its development, as well as preventive strategies. In this case series the data of all patients admitted with COVID-19 pneumonia to Khoula hospital intensive care unit (ICU) during the period from March 1st, 2020 to July 31st, 2021 were collected retrospectively and analyzed. Fourteen patients representing 7.1% out of the 196 ICU admissions had demonstrated one or more air leak manifestation. Male to female incidence was 3:1 and the mean age was 53 years. The 71.4% of these patients had received mechanical ventilation, 14.3% of them received continuous positive airway pressure (CPAP), and 14.3% just received oxygen supplementation via plain face mask. The average ventilation to air leak development time is around 7.6 days (95% CI: 1.9-13.4%). In conclusion, although the majority of the patients who had air leak were mechanically ventilated, the condition can develop in non-ventilated and even spontaneously breathing COVID-19 patients, and no specific ventilator measure could be blamed for its development. Lung-protective ventilation strategies and accurate timing for escalation of respiratory support are the mainstay for prevention.